(untitled) (KASBIT Business Journal, 2022)
Advertising is the most important influence in influencing consumers. The goal of advertising is to influence people to behave or buy a product in the way that the company wants them to. Ethical consumption is becoming a more popular marketing strategy, and companies are employing a range of strategies to persuade customers to buy socially acceptable items. Consumers are more likely to purchase ethically-sound products if they feel guilty, proud, afraid, or happy about it, according to a new study. A descriptive study with a sample size of 400 clients was carried out utilizing convenience sampling as a non-probability sampling technique, and the results are presented here. When conducting the study, SEM analysis was performed to determine the study’s hypothesis, and a questionnaire was employed to collect data. Emotional appeals are a surefire way to get a buyer to buy an ethically sound product, according to a study. so that they can attract clients who want to acquire products ethically. However, in the Pakistani context, pride appeal is irrelevant and will not compel Pakistani consumers to choose ethically decent goods. Using advertisements to evoke feelings of guilt, joy, and pride will be critical in persuading customers to behave in the way you want them to. As a result, we can confidently state that emotional appeals in advertising have the power to encourage people to make more ethical decisions.